Effects of Individual Differences and Exposure to the National Population And Family Development Board's Parenting Module On Parenting Outcomes - K Doshi, Anjli Panalal (1997)
The general purpose of this study was to determine the effectiveness of the National Population and Family Development Board's (NPFDB) parenting module among parents by examining the effects of individual differences (expressed readiness for parenting change and perceptions of parenting self-efficacy) and exposure to the module on parenting outcomes [parenting knowledge, attitudes, practices, and skills (parenting KAPS)]. The Pre-test-Post-test Control Group Design was used for evaluating the parenting module. The 80 respondents were randomly assigned to the experimental and control group. Results of the study showed that parenting KAPS improved significantly from before to after exposure for the experimental group. Generally, it was found that the participants had high perceptions of the module structure, usefulness and relevance of contents to their needs. Results suggested that individual differences was significantly correlated with parenting knowledge (r=0.56, p<0.05) and parenting attitudes (r= 0.46, p<0.05). However, there was no significant correlation between individual differences and parenting practices and skills. Results obtained suggested that exposure to the module was significantly and positively correlated with parenting knowledge (r=0.57, p<0.05), parenting attitudes (r=0.56, p<0.05), parenting practices (r=0.34, p<0.05) and parenting skills (r=0.26, p<0.05). There was a significant relationship (r=0.32, p<0.05) between individual differences and general perceptions of the module. )'he participants' exposure to the parenting module and individual differences was found to have a direct effect on their parenting KAP. However, for parenting skills there was no evidence to conclude that exposure to the module and individual differences explained the variation in parenting skills. The study concluded that the parenting module was effective in changing the parenting KAPS of parents.